2010
DOI: 10.7454/mst.v10i2.427
|View full text |Cite
|
Sign up to set email alerts
|

BIODEGRADASI SLUDGE MINYAK BUMI DALAM SKALA MIKROKOSMOS: Simulasi Sederhana Sebagai Kajian Awal Bioremediasi Land Treatment

Abstract: Telah dilakukan penelitian skala mikrokosmos yang bertujuan untuk melakukan uji kemampuan konsorsium mikroba hidrokarbonoklastik untuk meningkatkan degradasi sludge minyak bumi dengan perlakuan penambahan pupuk NPK sebagai sumber nitrogen. Percobaan secara aerobik dilakukan dengan meletakkan erlenmeyer pada shaker incubator dengan kecepatan putaran 120 rpm pada temperatur 50°C. Pengamatan selama 150 hari pada skala mikrokosmos menunjukkan konsorsium mampu tumbuh dengan baik hingga beban sludge mencapai 50% (v/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 5 publications
0
11
0
2
Order By: Relevance
“…Therefore, soil moisture is maintained in the range of 60-80 % due to soil microbes require sufficient moisture to grow [6]. Figure 5 shows a decrease in the pH of the soil due to lower soil moisture.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, soil moisture is maintained in the range of 60-80 % due to soil microbes require sufficient moisture to grow [6]. Figure 5 shows a decrease in the pH of the soil due to lower soil moisture.…”
Section: Resultsmentioning
confidence: 99%
“…Below pH 5 and above 8.5, the bacteria cannot grow well unless the bacteria resistant to acid and alkaline [4]. On the other hand, the availability of oxygen is another environmental factor that is important in the biodegradation of oil [6]. Aeration is one way to provide oxygen for the microbes.…”
Section: Resultsmentioning
confidence: 99%
“…Cookson (1995) stated that hydrocarbons are used as sources of nutrients and energy sources by microbes. Furthermore, Nugroho (2006) stated that the abundance and diversity of microorganisms in nature has a positive correlation with the percentage of oil degradation. Figure 4 showed that almost all treatments have optimum soil moisture content with an average of 25 -34%.…”
Section: Discussionmentioning
confidence: 99%
“…Measurements of soil moisture content were carried out to monitor soil water content in the reactor. Water content affects the onset of contamination, gas transfer, and the growth of microorganisms (Nugroho 2006). At the optimum moisture, microorganisms are active and grow faster.…”
Section: Measurement Of Soil Moisture Contentmentioning
confidence: 99%
“…After the stationary phase is followed by a decrease because the number of bacteria is out of balance with the availability of nutrients. According to Nugroho (2012), hydrocarbon bacteria in their life activities require carbon molecules as a source of nutrition and energy to metabolize and reproduce. Another factor that affects the reduction in bacterial cell density is that there is a lack of nutrients such as N, P and C that are no longer suitable for growth.…”
Section: Bacterial Densitymentioning
confidence: 99%